Transboundary aquifers of Africa: Review of the current state of knowledge and progress towards sustainable development and management - Nijstena, G-J.; Christelis, G.; Villholth, Karen G.; Braune, E.; Gaye, B.C. (Elsevier, 2018)
Study region : Transboundary aquifers (TBAs) of Africa. Study focus: Review of work on TBAs in Africa, including an overview of assessments and management efforts that have taken place over the last half century. New hydrological insights : Seventy-two TBAs have been mapped in Africa. They underlie 40% of the continent, where 33% of the population lives, often in arid or semi-arid regions. TBA inventories have progressed since 2000 and remain work in progress. Despite their importance only eleven TBAs have been subjected to more detailed studies. Cooperation has been formalised for seven TBAs. Most of these TBAs are in North Africa and the Sahel. The recent global Transboundary Waters Assessment Programme compiled information at the national level to describe TBAs in terms of key indicators related to the water resource, socio-economic, and legal and institutional conditions. Availability of data at national level is low, hampering regional assessment. Comparing indicators, from questionnaire surveys, with those from a global water-use model showed variable levels of agreement, calling for further research. Reports on agreements scoping TBA management, indicate that this may be dealt with within international river/lake agreements, but reported inconsistencies between TBA sharing countries also indicate that implementation is limited. Increasing awareness and support to joint TBA management is noticeable amongst international organisations. However, such cooperation requires long-term commitment to produce impacts at the local level.